COVID‐19 in people living with HIV: Clinical implications of dynamics of the immune response to SARS‐CoV‐2. Issue 3 (8th October 2020) - Mondi, Annalisa; Cimini, Eleonora; Colavita, Francesca; Cicalini, Stefania; Pinnetti, Carmela; Matusali, Giulia; Casetti, Rita; Maeurer, Markus; Vergori, Alessandra; Mazzotta, Valentina; Gagliardini, Roberta; De Zottis, Federico; et al.
Abstract: Little evidence on coronavirus disease 2019 (COVID‐19) in people living with HIV (PLWH) is currently available. We reported clinical and viroimmunological data of all HIV‐positive patients admitted to our center with COVID‐19 from March 1 to May 12, 2020. Overall, five patients were included: all were virologically‐suppressed on antiretroviral therapy and CD4+ count was greater than 350 cell/mm 3 in all but two patients. Although all patients had evidence of pneumonia on admission, only one developed respiratory failure. Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNA was never detected from nasopharyngeal swabs in two patients, whereas in the others, viral clearance occurred within a maximum of 43 days. Immunoglobulin G production was elicited in all patients and neutralizing antibodies in all but one patient. Specific‐T‐cell response developed in all patients but was stronger in those with the more severe presentations. Similarly, the highest level of proinflammatory cytokines was found in the only patient experiencing respiratory failure. Despite a mild presentation, patients with more pronounced immunosuppression showed high degrees of both cytokines production and immune activation. Our study did not find an increased risk and severity of COVID‐19 in PLWH. Adaptative cellular immune response to SARS‐CoV‐2 appeared to correlate to disease severity. The mild clinical picture showed in advanced HIV patients, despite a significant T‐cell activation and inflammatory profile, suggests a potential role of HIV‐driven immunological dysregulation in avoiding immune‐pathogenetic processes. However, other possible explanations, as a protective role of certain antiretroviral drugs, should be considered. Further larger studies are needed to better clarify the impact of HIV infection on COVID‐19. Highlights: The clinical course of COVID‐19 and the dynamics of the immune response to SARS‐CoV‐2 infection in people living with HIV have not yet been fully elucidated Indeed, although worse outcomes might be expected in HIV‐positive patients compared to the general population, it has been supposed that the HIV‐related immune dysregulation could paradoxically mitigate the hyperinflammation syndrome responsible for the most severe complications of SARS‐CoV‐2 infection. In this case series we did not find an increased risk of both acquiring and having a severe course of COVID‐19 in people living with HIV compared to how reported in the general population. We observed that patients with more severe HIV‐related immunosuppression, despite the development of a specific immune response and the presence of a strong cellular immune‐activation and a moderate inflammatory profile, experienced a mild/moderate disease. These findings might suggest that the lower and impaired immune reactivity of advanced HIV infection could contribute to avoid immune‐pathogenetic processes. However, other possible explanations, as a potential protective role of certain antiretroviral regimens, should be considered.